The fight for free speech : ten cases that define our First Amendment freedoms - Rosenberg, Ian (New York : New York University Press, 2021)
"Media lawyer Ian Rosenberg distills the spectrum of free speech law down to ten critical issues. Each chapter in this book focuses on a contemporary free speech question--from student walkouts for gun safety to Samantha Bee's expletives, from neo-Nazis marching in Charlottesville to the muting of adult film star Stormy Daniels-- and then identifies, unpacks, and explains the key Supreme Court case that provides the answers"--Provided by the publisher.
1. The Women's March and the marketplace of ideas -- 2. Take a knee and the Pledge of Allegiance -- 3. Libel, actual malice, and the civil rights movement -- 4. Student speech from the Vietnam War to the National School Walkout -- 5. Stormy Daniels, prior restraints, and the Pentagon Papers -- 6. Flipping off the president and fuck the draft -- 7. Samantha Bee, seven dirty words, and indecency -- 8. Saturday Night Live, Hustler, and the power of parody -- 9. Nazis in Charlottesville, funeral protests, and speakers we hate -- 10. Social media and the "vast democratic forums of the Internet".
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 16, 2021).
eBooks on EBSCOhost
Keywords: United States; Constitution (United States); United States; Freedom of speech -- United States; Liberté d'expression -- États-Unis.; Civil Rights; LAW; Freedom of speech; United States; Freedom of speech -- United States; Freedom of speech -- United States; Electronic books; decisions (judicial records); Court decisions and opinions; Court decisions and opinions; Recueils de jurisprudence et d'opinions.